Infographics as an assignment to build digital skills in the social work classroom. Issue 2 (3rd July 2019) - Jones, Nathalie P.; Sage, Melanie; Hitchcock, Laurel
Abstract: According to the theory of experiential learning, ideal learning happens in contexts that offer concrete experiences and active experimentation alongside abstract and reflective learning. Bloom's Taxonomy suggests that higher-order thinking skills include creating, designing, and producing information, whereas, classroom assignments often reinforce lower-level thinking such as interpreting, explaining, and comparing. Higher-order learning assignments include situations in which students can experiment with product generation for real-world situations, reflect on the relationship between theory and practice, and receive specific feedback about their efforts. Social work educators can create these situations by incorporating infographics in the classroom. This research finds that social work students assigned an infographics project in three different universities say it improved their engagement and learning, and offered opportunities for creativity and decision making.